Superiority of stapled side-to-side gastrojejunostomy over conventional hand-sewn end-to-side gastrojejunostomy for reducing the risk of primary delayed gastric emptying after subtotal stomach-preserving pancreaticoduodenectomy - Murata, Yasuhiro; Tanemura, Akihiro; Kato, Hiroyuki; Kuriyama, Naohisa; Azumi, Yoshinori; Kishiwada, Masashi; Mizuno, Shugo; Usui, Masanobu; Sakurai, Hiroyuki; Isaji, Shuji (Surgery today (Tokyo, Japan), 2017)
Background and purpose Delayed gastric emptying (DGE) is the most common complication following pancreaticoduodenectomy (PD). The clinical efficacy of stapled side-to-side anastomosis using a laparoscopic stapling device during alimentary reconstruction in PD is not well understood and its superiority over conventional hand-sewn end-to-side anastomosis remains controversial. The objective of this study was to evaluate the effectiveness of the stapled side-to-side anastomosis in preventing the development of DGE after PD. Methods The subjects of this retrospective study were 137 patients who underwent pancreaticoduodenectomy, as subtotal stomach-preserving pancreaticoduodenectomy (SSPPD; n = 130), or conventional whipple procedure ( n = 7) with Child reconstruction, between January 2010 and May 2014. The patients were divided into two groups according to whether they had had a stapled side-to-side anastomosis (SA group; n = 57) or a conventional hand-sewn end-to-side anastomosis (HA group; n = 80). Results SA reduced the operative time (SA vs. HA: 508 vs. 557 min, p = 0.028) and the incidence of delayed gastric emptying (SA vs. HA: 21.1 vs. 46.3%, p = 0.003) and was associated with shorter hospitalization (SA vs. HA: 33 vs. 39.5 days, p = 0.007). In this cohort, SA was the only significant factor contributing to a reduction in the incidence of DGE ( p = 0.002). Conclusions Stapled side-to-side gastrojejunostomy reduced the operative time and the incidence of DGE following PD with Child reconstruction, thereby also reducing the length of hospitalization.